PENGARUH DISIPLIN KERJA DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU SMP N 1 LASEM - Indah Wahyuni; Dian Ayu Liana Dewi (JURNAL ILMIAH EDUNOMIKA, 2026)
The purpose of this study was to evaluate the influence of work discipline and school culture on teacher performance at SMP N 1 Lasem. The approach used was quantitative with population of 41 teachers, and sampling using a saturated sampling technique where all members of yhe population were used as samples. Data collection was carried out through a questionnaire that included indicators of work discipline and school culture. The data analysis technique used multiple linear regression. The results showed that work discipline and school culture had a positive and significant effevt on teacher performance at SMP N 1 Lasem. Simultaneously, these two variables explained 77,5% of the variation in teacher performance. Thus, improving work discipline and school culture will improve teacher performance. Keywords: Work Discipline, School Culture, Teacher Performance.